Density of Langerhans cells in the keratocystic odontogenic tumor Densidade das células de Langerhans no tumor odontogênico queratocístico - Thiago Martins Meira; Leonardo Araújo Melo; Clarissa Araújo Silva Gurgel; Eduardo Antônio Gonçalves Ramos; Luciano Cincurá Santos; Waldécio dos Santos Vita; Jean Nunes dos Santos (Sociedade Brasileira de Patologia Clínica, 2010)
INTRODUCTION: Keratocystic odontogenic tumors (KOTs) are distinct odontogenic lesions commonly affecting the mandible bones. Langerhans cells (LCs) are specialized dendritic cells responsible for the presentation of antigens to T lymphocytes in mucosal and cutaneous surfaces. OBJECTIVE: This study analyzed the immunohistochemical expression of LCs in KOTs. MATERIALS AND METHODS: Fifteen cases of KOTs were studied using the anti-CD1a marker. Results: LCs were observed in all 15 cases analyzed. They were found to be concentrated in areas of cystic epithelial hyperplasia, mainly in those areas presenting higher concentration of inflammatory cells. Furthermore, a significant association between the number of LCs and areas of cystic epithelium presenting hyperplasia (Mann-Whitney test, p = 0.0223) was observed. The shape and location of these cells in KOTs epithelium were variable. CONCLUSION: The lower number of LCs observed on atrophic cystic epithelium of KOTs may be due to decreased epithelial immunosurveillance and this may result in locally aggressive invasiveness. INTRODUÇÃO: Tumor odontogênico queratocístico (TOQ) é uma lesão odontogênica de caráter distinto que afeta frequentemente ossos maxilares. Células de Langerhans (CLs) são células dendríticas especializadas, responsáveis pela apresentação de antígenos aos linfócitos T nas superfícies cutânea e mucosa. OBJETIVO: Este estudo analisou a expressão imuno-histoquímica das CLs em lesões de TOQ. MATERIAIS E MÉTODOS: Quinze casos de TOQ foram estudados utilizando o marcador anti-CD1a. RESULTADOS: As CLs foram observadas em todos os 15 casos analisados. Essas células estavam concentradas em áreas de hiperplasia do epitélio cístico, especialmente naquelas que apresentavam alta concentração de células inflamatórias. Em adição, foi encontrada associação significativa entre número de CLs e áreas do epitélio cístico que apresentavam hiperplasia (Mann-Whitney test, p = 0.0223). O formato e a localização dessas células no epitélio dos TOQs foram variáveis. CONCLUSÃO: O menor número de CLs encontrado no revestimento cístico atrófico dos TOQs pode ser atribuído à imunovigilância deficiente e isso pode resultar em comportamento biológico localmente agressivo.